Analisis Implementasi Sistem Informasi Pengajuan Pas Bandara Sultan Thaha Jambi dengan Blackbox Testing - Randi Artino; Yuniar Istiyani (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2025)
Sultan Thaha Airport, Jambi, is one of the airports that has implemented a digital Airport PAS application process through a website-based system. This application information system is designed to improve efficiency and effectiveness in the PAS (Personal Airport Security) application process, which was previously done manually. With this system, it is expected that the entire administrative process can run faster, more transparently, and minimize errors. The purpose of this study is to analyze the implementation of the e-PAS information system, and to identify obstacles that arise in its implementation in the work environment of Sultan Thaha Airport, Jambi. The research method used is descriptive qualitative, with a blackbox testing approach to test the system's functionality. Data collection techniques were carried out through direct observation, interviews with 3 PAS applicants and 6 operational officers, and documentation related to system use. The data obtained were analyzed through the process of data reduction, data presentation, as well as drawing conclusions and verification. Data validity testing was carried out using the source and technique triangulation method. The results of the study indicate that the implementation of the e-PAS system has run quite well. However, several technical challenges remain, hindering the smooth running of the process, such as disruptions to the data input system, challenges with information validation, and suboptimal or incomplete system features. These findings provide important input for system developers to make continuous improvements to ensure more effective and efficient services in the future. Improved training for staff is also necessary to ensure optimal system utilization. Furthermore, regular evaluations of system performance are mandatory to maintain consistent service quality.